Equality of Member States as a New Rationale for the Principle of Primacy and Its Significance for the Constitutionalisation of EU Law (Polish Yearbook of International Law, 2025)
In its recent jurisprudence the Court of Justice of the European Union (CJEU) has indicated new grounds for the principle of primacy of EU law: the equality of Member States before the Treaties. This reflects the view that the principle of primacy should not be perceived within a bilateral framework – as a means of resolving conflicts between two legal orders (EU and national) – but in a multilateral context, where uniformity, equality and primacy are strongly intertwined. The aim of this paper will be to analyse and assess the CJEU stance on this new foundation of the principle of primacy. It will be argued that the CJEU seeking justification for the principle of primacy in arguments of an axiological nature, not only functional ones, is expected and justified after the Treaty of Lisbon and in the face of the current threats to the values embedded in Art. 2 of the Treaty on European Union. It is crucial for further strengthening of the processes of constitutionalisation of EU law. However, controversy may arise from the views that such new argumentation on the rationale of the primacy principle already resolves the competing claims of final authority in the EU.